The plight of the diasporic Muslim refugees living in the west - Abdul Razak, Mohd Abbas; Mustapha, Maziah (Al-Hikmah Research and Publication Centre, 2024)
The origin of the word diaspora goes back to the Greek language. It explains the condition of people who have been displaced, dispersed and scattered from their homeland. Western literature and media highlight the word diaspora exclusively referring to the suffering of the Jewish community in the bygone history of the world. In truth, this word is not only applicable to the Jews but to others as well, including the Muslims. Generally, a diasporic nation or community is forced to leave their homeland due to unfavourable or hostile conditions they have to face. Hostility faced by the diasporic community can be due to internal factors like sectarian violence, an oppressive regime, racism, genocide, etc. within their homeland. Sometimes, a diasporic situation is also triggered by external factors like the intrusion of a foreign army, the imminence of war, the annexation of a country by its neighbour, etc.With this chapter of the book, we would like to explore the plight of the diasporic Muslim community in the West. Among others, this chapter will cover subheadings like; what are the conditions that force the Muslims to flee their homeland, what are the problems endured by Muslim refugees in Western countries, what guiding principles should the diasporic Muslim community follow to coexist with others, Ethics that should be observed by Muslim refugees, and finally what the West has to do to avoid the influx of refugees from the Muslim world. As a qualitative research, the researchers will employ textual and contextual analysis methods to analyze the relevant data that will be retrieved from print and internet sources.